1986
DOI: 10.1073/pnas.83.19.7557
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the in vivo parathyroid hormone-mediated calcemic response in rats by a synthetic hormone antagonist.

Abstract: The parathyroid hormone (PTH) analog, METHODSThe PTH antagonist [Tyr 34 ]bPTH-(7-34)-amide and the synthetic fragment human (h) PTH-(1-34) were synthesized by the solid-phase method of Merrifield and co-workers (11-13) using modifications described (14). The peptides were purified by gel-filtration chromatography followed by semipreparative HPLC (15,20). hPTH-(1-34) and the antagonist were dissolved in diluent immediately prior to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Others have demonstrated that smaller C-PTH fragments do not react with the PTH/PTHrP receptor, and that region 69 -84 has to be intact to react with the C-PTH receptor (15). The anticalcemic and antiphosphaturic effects of this PTH peptide in vivo were demonstrated at higher molar concentrations and were mediated by an inhibition of hPTH-(1-34) binding to the PTH/PTHrP receptor and of ligand-induced cAMP production (42,43). This last point was also demonstrated in a recent study (40).…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that smaller C-PTH fragments do not react with the PTH/PTHrP receptor, and that region 69 -84 has to be intact to react with the C-PTH receptor (15). The anticalcemic and antiphosphaturic effects of this PTH peptide in vivo were demonstrated at higher molar concentrations and were mediated by an inhibition of hPTH-(1-34) binding to the PTH/PTHrP receptor and of ligand-induced cAMP production (42,43). This last point was also demonstrated in a recent study (40).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of residues 1–6 from the PTH(1–34) scaffold produced analogues that no longer activate signalling via the cAMP–PKA pathway, but instead, function as competitive antagonists of PTHR1-mediated cAMP signalling. 36 Further modification of the PTH(7–34) scaffold at residue position 12 produced an analogue, DTrp 12 -PTH(7–34), which in addition to competitively antagonizing cAMP signalling at PTHR1, 37 also acts as an inverse agonist and consequently reduces basal cAMP signalling at certain constitutively active PTHR1 variants. 38 Other PTH and PTHrP ligand analogues modified at residue position 1 have been developed that preferentially activate Gα S -cAMP signalling over Gα q -PLC-ÎČ signalling.…”
Section: Altered Signalling Of Pthr1 Ligandsmentioning
confidence: 99%
“…Combined removal of Ser/Ala 1 and Val 2 virtually eliminates adenylyl cyclase activation. Peptides lacking the first three to six amino acids are inhibitors of PTH action (23,42).…”
Section: Effects Of Pth On Receptor Activation and Receptor Turnovermentioning
confidence: 99%